If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + -1 = x + 26 Reorder the terms: -1 + -8x = x + 26 Reorder the terms: -1 + -8x = 26 + x Solving -1 + -8x = 26 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -1 + -8x + -1x = 26 + x + -1x Combine like terms: -8x + -1x = -9x -1 + -9x = 26 + x + -1x Combine like terms: x + -1x = 0 -1 + -9x = 26 + 0 -1 + -9x = 26 Add '1' to each side of the equation. -1 + 1 + -9x = 26 + 1 Combine like terms: -1 + 1 = 0 0 + -9x = 26 + 1 -9x = 26 + 1 Combine like terms: 26 + 1 = 27 -9x = 27 Divide each side by '-9'. x = -3 Simplifying x = -3
| -4x-9=x+1 | | -3w+5=7w-3 | | 12x^4-4x^2-5=0 | | -3x+8=x-4 | | 2a+17=6a+5 | | -3u+10=5u+3 | | 5x+1=12-x | | 5p+1=3p+13 | | 5=z+7 | | 5=z-1 | | 5=z-12 | | -0.25*x^2+1.25*x+1=0 | | -0.25*x^2+1.25*x-1=0 | | 0.25*x^2+1.25*x+1=0 | | -×=-3/4 | | h=-16t^2+224t | | 0.25*x^2+1.25*x-1=0 | | 7(1-x)/10=1 | | 3+(5+a)=(3+5)+a | | 2x(24/3)-2= | | 174/36 | | x^3+15x^2=x^2-49x | | 2x^4-14x^3-60x^2=0 | | 10x+6x=48 | | 120(x/100)=1 | | 70(1-x)/100=1 | | 7(1-x)=1 | | 5/6x-3x=23 | | 7/2x-5/6x=1 | | 4s^2-11s=-7 | | 12y-50x=1500 | | 9=5x-69 |